Modeling tissue-selective cavitation damage. (15th November 2019) - Mancia, Lauren; Vlaisavljevich, Eli; Yousefi, Nyousha; Rodriguez, Mauro; Ziemlewicz, Timothy J; Lee, Fred T; Henann, David; Franck, Christian; Xu, Zhen; Johnsen, Eric
Abstract: The destructive growth and collapse of cavitation bubbles are used for therapeutic purposes in focused ultrasound procedures and can contribute to tissue damage in traumatic injuries. Histotripsy is a focused ultrasound procedure that relies on controlled cavitation to homogenize soft tissue. Experimental studies of histotripsy cavitation have shown that the extent of ablation in different tissues depends on tissue mechanical properties and waveform parameters. Variable tissue susceptibility to the large stresses, strains, and strain rates developed by cavitation bubbles has been suggested as a basis for localized liver tumor treatments that spare large vessels and bile ducts. However, field quantities developed within microns of cavitation bubbles are too localized and transient to measure in experiments. Previous numerical studies have attempted to circumvent this challenge but made limited use of realistic tissue property data. In this study, numerical simulations are used to calculate stress, strain, and strain rate fields produced by bubble oscillation under histotripsy forcing in a variety of tissues with literature-sourced viscoelastic and acoustic properties. Strain field calculations are then used to predict a theoretical damage radius using tissue ultimate strain data. Simulation results support the hypothesis that differential tissue responses could be used to design tissue-selective treatments. Results agree with studies correlating tissue ultimate fractional strain with resistance to histotripsy ablation and are also consistent with experiments demonstrating smaller lesion size under exposure to higher frequency waveforms. Methods presented in this study provide an approach for modeling tissue-selective cavitation damage in general.